Assessing simple policy rules: a view from a complete macro model - Eric M. Leeper; Tao Zha (Federal Reserve Bank of Atlanta, 2000)
We explore two popular approaches to empirical analysis of monetary policy: the New Keynesian and the identified vector autoregression approaches. Stylized models of private behavior coupled with simple rules describing policy behavior characterize New Keynesian work. Vector autoregressions consist of minimally identified dynamic descriptions of private behavior coupled with a detailed rule for policy behavior. The simplicity of New Keynesian models aids in communication but leaves the models' implications vulnerable. By relating the New Keynesian models to identified vector autoregressions, we explore the differences and similarities in the two approaches and assess some of the key conclusions to emerge from New Keynesian research.
Keywords: 330; Vector autoregression; Monetary policy; Forecasting